2018
DOI: 10.7570/jomes.2018.27.4.233
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Fecal Calprotectin in Obese Children and Adults

Abstract: Background Obesity is a complex, medical condition causally contributing to many chronic diseases and a number of efforts have been made to find the associated markers for novel prevention and treatment of obesity. Our study was to evaluate the relationship between gut immune response and obesity and overweight with use of fecal calprotectin (FC) both in adult and children groups. Methods Fecal samples were obtained from 74 subjects: 14 non-obese and overweight children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
(23 reference statements)
1
9
1
Order By: Relevance
“…Obesity was previously shown to be associated with increased fecal calprotectin concentrations as a marker of gastrointestinal inflammation in adult people (Kant et al, 2013;Poullis et al, 2004;Verdam et al, 2013) and children (Spagnuolo et al, 2010). However, other studies have produced conflicting results of either no association of obesity with increased fecal calprotectin concentrations in adults (Brignardello et al, 2010) or only in adults but not in children, suggesting a difference in the pathophysiology of obesity between adults and children (Park & Kim, 2018). Interestingly, increases in fecal calprotectin concentrations were associated with changes in the gastrointestinal microbiome in one human study (Verdam et al, 2013), and changes in the gastrointestinal microbial profiles were shown to also differ between healthy lean and healthy obese dogs in one investigation by our group (Handl et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity was previously shown to be associated with increased fecal calprotectin concentrations as a marker of gastrointestinal inflammation in adult people (Kant et al, 2013;Poullis et al, 2004;Verdam et al, 2013) and children (Spagnuolo et al, 2010). However, other studies have produced conflicting results of either no association of obesity with increased fecal calprotectin concentrations in adults (Brignardello et al, 2010) or only in adults but not in children, suggesting a difference in the pathophysiology of obesity between adults and children (Park & Kim, 2018). Interestingly, increases in fecal calprotectin concentrations were associated with changes in the gastrointestinal microbiome in one human study (Verdam et al, 2013), and changes in the gastrointestinal microbial profiles were shown to also differ between healthy lean and healthy obese dogs in one investigation by our group (Handl et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The calgranulin ratio in feces (fCalR) has not been evaluated or reported in humans or dogs with gastrointestinal conditions. Fecal S100/calgranulin concentrations were shown to be affected by increasing age, obesity, diet and also other lifestyle factors in people (Mendall et al, 2016;Park & Kim, 2018;Poullis et al, 2004). However, knowledge about the effects of patient factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calprotectin has one of the most critical roles in gut immunity, which is not only related to IBD but also to obesity. FC levels in obese and overweight adults were observed to be significantly higher compared to obese and overweight children in age-obesity studies [10].…”
mentioning
confidence: 83%
“…The provided stool samples were subdivided and stored at −80°C, until use. The measurement used for FC detection followed Park and Kim's [10]. measurements.…”
Section: Fecal Calprotectinmentioning
confidence: 99%